The application of nanostructured lipid carrier for encapsulation of Rosa canina and Heracleum persicum extracts and production of mayonnaise enriched with encapsulated extracts - Hadi Dehghani Khiavi; Maryam Khakbaz Heshmati; Saeed Dadashi; Akram Pezeshki; Babak Ghanbarzadeh (Journal of Agriculture and Food Research)
Due to the increasing demand for healthy foods, scientists are looking for a way (encapsulation) to use extracts containing bioactive compounds to extend the shelf life of food products without changing their organoleptic properties. In this study, mayonnaise enriched with a nanostructured lipid carrier (NLC) loaded with Rosa canina L. and Heracleum persicum extract (RAE-NLC) was produced as a new formulation. The best NLC was determined based on particle size and polydispersity index (lowest values), which can ensure high system stability for subsequent processes, and then its characteristics were investigated using a zetasizer, scanning electron microscope (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). According to the results of dynamic light scattering (DLS), the best carrier (margarine (350 mg), pomegranate seed oil (liquid oil) (150 mg), Tween 80 (250 mg), and polyglycerol ester (250 mg)) had smaller particle size (103.5 nm) and polydispersity index (0.180) values than other carriers. SEM images showed smooth surface spherical particles with smaller particle size. After 60 days of storage, the particles in the RAE-NLC solution remained at 104.5 nm with a unimodal distribution. The yield (EY%) and encapsulation efficiency (EE%) were calculated to be 81.37 % and 83.50 %, respectively. Considering the development of new hydrogen bonds and amorphous structure of RAE-NLC, FTIR and XRD investigations showed that RAE was well inserted and uniformly embedded in the NLC. Furthermore, the results showed that the addition of nanocarriers including RAE to mayonnaise can lead to maximum acceptability due to the reduction of undesirable characteristics such as color, aroma, and taste of the extract (RAE). Also, considering the antioxidant properties of RAE-NLC polyphenols, after 60 days, this formulation has the maximum DPPH inhibition (%) and the minimum peroxide value (meqO2/kgOil). Finally, RAE-NLC plays an important role in increasing the shelf life of mayonnaise by introducing a new formulation of nanostructured lipid carriers containing plant extracts.